Selectfluor and NFSI exo‐Glycal Fluorination Strategies Applied to the Enhancement of the Binding Affinity of Galactofuranosyltransferase GlfT2 Inhibitors. Issue 46 (24th September 2014) - Dumitrescu, Lidia; Eppe, Guillaume; Tikad, Abdellatif; Pan, Weidong; Bkassiny, Sandy El; Gurcha, Sudagar S.; Ardá, Ana; Jiménez‐Barbero, Jesús; Besra, Gurdyal S.; Vincent, Stéphane P.
Abstract Two complementary methods for the synthesis of fluorinated exo‐glycals have been developed, for which previously no general reaction had been available. First, a Selectfluor‐mediated fluorination was optimized after detailed analysis of all the reaction parameters. A dramatic effect of molecular sieves on the course of the reaction was observed. The reaction was generalized with a set of biologically relevant furanosides and pyranosides. A second direct approach involving carbanionic chemistry and the use of N‐fluorobenzenesulfonimide (NFSI) was performed and this method gave better diastereoselectivities. Assignment of the Z/E configuration of all the fluorinated exo‐glycals was achieved based on the results of HOESY experiments. Furthermore, fluorinated exo‐glycal analogues of UDP‐galactofuranose were prepared and assayed against GlfT2, which is a key enzyme involved in the cell‐wall biosynthesis of major pathogens. The fluorinated exo‐glycals proved to be potent inhibitors as compared with a series of C‐glycosidic analogues of UDP‐Galf, thus demonstrating the double beneficial effect of the exocyclic enol ether functionality and the fluorine atom.